Creative Drama and Eradication of Examination Malpractice Among University of Calabar Students - Yta, Edisua Merab; Stephen, Eko Dennis; Wonah, Godwin (PINISI Discretion Review, 2021)
Examination malpractice has shown up to be one of the most disturbing socio-behavioural challenges of the Nigerian society. It keeps deepening despite attempts made to curb it. This paper on Creative Drama and Examination Malpractice among University of Calabar Studentsis aimed at providing a more integral approach to solving the menace. It presents Creative Drama as an alternative learning approach that can make students learn in manners that help deeper understanding, better memory retentivity and excellent recall using content analysis method to explore earlier experiments on Creative Drama a more effective pedagogical tool than the traditional practice currently used in University of Calabar and in Nigeria educational system generally. The findings show Creative Drama a more excellent and effective teaching approach for science, technical and arts courses. Therefore, the introduction and use Creative Drama as a teaching and learning approach is presented as the most effective strategy for taming examinationmalpractice in the University of Calabar and Nigeria.Â